KEPEMILIKAN DAN STRUKTUR MANAJERIAL : PERAN MEDIASI KOMPLEKSITAS TERHADAP KINERJA PERUSAHAAN MANUFAKTUR KONSUMSI PRIMER INDONESIA - Christmasya Amelia; Elok Heniwati; Syarif M. Helmi (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study seeks to evaluate the impact of ownership and managerial structure on the financial performance of primary consumption sector manufacturing firms listed on the Indonesia Stock Exchange (IDX), while also investigating the mediating role of organizational structure complexity. This research employs a quantitative methodology utilizing PLS-SEM analysis tools via SmartPLS 4.0 software. The sample comprises 36 enterprises chosen by purposive sampling from 2021 to 2024. The research findings indicate that both management ownership and managerial structure exert a significantly positive influence on financial success. The complexity of the organizational structure has been shown to adversely mediate the relationship between ownership and managerial structure on financial performance, indicating that increased complexity correlates with a drop in the company's performance. These findings corroborate agency theory and contingency theory, highlighting the significance of congruence between organizational structure and managerial responsibilities in enhancing corporate success. This research enhances the comprehension of internal governance and organizational design's influence on obtaining optimal financial performance.